Determinación del crecimiento de cepas lactobacillus plantarum (22 lmc 41 y lmc) a diferentes niveles de ph, temperatura y sales biliares - Vélez Arteaga, Edison Stalin (2018)
The growth of strains of Lactobacillus plantarum (22 Lmc and 41 Lmc) was determined by non-descriptive statistical formulas, a DCA was used with a bifactorial arrangement, for the temperature 6 treatments with 4 repetitions were used; for pH, 10 treatments with 4 repetitions were used and for the effect the bile salts were used 4 treatments and 12 repetitions; the strains were measured by Optical Density (OD) by means of a JENWAY 6305 UV spectrophotometer at a wavelength of 560 nm and a factor of 0.9; at 3 temperature levels, where both strains had favorable growth between 30 ° C to 45 ° C at 24 and 48 hours, with their highest development peak at 45 ° C. In the same way, in the determination of the growth of the strains at different pH levels, the highest point of growth was 4.0 in both strains, also developing favorably in the levels 7.5 - 6.7 - 3.4. For the calculation of resistance to bile salts, at 3 and 6 o'clock the strains 41 Lmc and 22 Lmc obtained a greater development in the presence of bile salts than in the absence thereof, with the 41 Lmc strain being more prominent. It is concluded that there was a favorable survival and growth in the different levels of temperature, pH and established bile salts, which would indicate that the strains could be used for the preparation of biopreparations with probiotic potential for animal production purposes.